Upaya UMKM Kelurahan Jambangan Surabaya Untuk Onboarding ke Dalam Ekosistem Digital - Dhyah Harjanti; Wilma Laura Sahetapy (Fakultas Ekonomi, Universitas PGRI Adi Buana Surabaya, 2022)
The use of digital technology has become a demand for business people, including MSMEs. Various applications of social media are available to support business activities at a very affordable cost. However, the number of MSME actors using social media to market their products is still low. This community service activity provides understanding and assistance regarding social media usage as a marketing tool to MSME actors, especially MSME actors in Jambangan Village, Jambangan District, Surabaya. This activity received a positive response from SMEs. From this activity, MSME actors become more confident and motivated to use social media in their business and gain new knowledge and skills regarding ways, tricks, and tips for using social media as a marketing tool. The use of digital technology has become a demand for business people, including MSMEs. Various applications of social media are available to support business activities at a very affordable cost. However, the number of MSME actors using social media to market their products is still low. This community service activity provides understanding and assistance regarding social media usage as a marketing tool to MSME actors, especially MSME actors in Jambangan Village, Jambangan District, Surabaya. This activity received a positive response from SMEs. From this activity, MSME actors become more confident and motivated to use social media in their business and gain new knowledge and skills regarding ways, tricks, and tips for using social media as a marketing tool.